2010
DOI: 10.1038/jhg.2010.124
|View full text |Cite
|
Sign up to set email alerts
|

The ENPP1 K121Q polymorphism is not associated with type 2 diabetes or obesity in the Chinese Han population

Abstract: Type 2 diabetes (T2D) mellitus is a metabolic disorder characterized by chronic hyperglycemia and insulin resistance. It has been a worldwide public health problem, which is increasing rapidly, especially in developing countries such as China. The ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) gene, also known as plasma cell membrane glycoprotein 1, has been reported by genetic association studies as being associated with T2D and obesity in various populations, such as Caucasian and African America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 43 publications
2
14
1
Order By: Relevance
“…The ENPP1 rs1044498 SNP has been reported to increase the risk of acquiring T2D in South Asians residing in the USA (Abate et al, 2005), India (Abate et al, 2005), and Taiwan (Wang et al, 2012). In contrast, this association has not been replicated in Japanese (Keshavarz et al, 2006), Taiwanese (Chen et al, 2006), Korean (Seo et al, 2008), Indian (Bhatti et al, 2010), and Chinese (Zhao et al, 2011;Shi et al, 2011) populations. Several meta-analysis studies have also suggested that the ENPP1 rs1044498 SNP is associated with an increased risk of developing T2D in European and Asian populations Li, 2012;Jing et al, 2012;Tang et al, 2014).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…The ENPP1 rs1044498 SNP has been reported to increase the risk of acquiring T2D in South Asians residing in the USA (Abate et al, 2005), India (Abate et al, 2005), and Taiwan (Wang et al, 2012). In contrast, this association has not been replicated in Japanese (Keshavarz et al, 2006), Taiwanese (Chen et al, 2006), Korean (Seo et al, 2008), Indian (Bhatti et al, 2010), and Chinese (Zhao et al, 2011;Shi et al, 2011) populations. Several meta-analysis studies have also suggested that the ENPP1 rs1044498 SNP is associated with an increased risk of developing T2D in European and Asian populations Li, 2012;Jing et al, 2012;Tang et al, 2014).…”
Section: Introductionmentioning
confidence: 72%
“…Several meta-analysis studies have also suggested that the ENPP1 rs1044498 SNP is associated with an increased risk of developing T2D in European and Asian populations Li, 2012;Jing et al, 2012;Tang et al, 2014). While the ENPP1 rs1044498 SNP has been associated with obesity in Austrian and French subjects (Meyre et al, 2005), a case-control study in Chinese subjects revealed that there was no association (Zhao et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…A major function of NPP1 is in bone mineralization and soft-tissue calcification [8][9][10]. Moreover, NPP1 has also been linked to insulin resistance and type 2 diabetes [11][12][13][14][15]. NPP2 has been shown to promote cancer cell invasion, cell migration, lymphocyte trafficking and angiogenesis [1,16].…”
Section: Introductionmentioning
confidence: 98%
“…Our results are similar to those of a vast majority of studies carried out in different populations. No evidence for an association of the ENPP1 K121Q variant with insulin resistance or type 2 diabetes was reported in Japanese [38], Spanish [39], Danish Caucasian [40], North Indian [13], UK Caucasian [41], and Chinese [42] populations. Besides, a great difference in allele frequencies was observed between the different populations [26,36,43].…”
Section: Discussionmentioning
confidence: 99%